Dielectric Anisotropy Properties of BAC-Doped 5CB Liquid Crystal - Ozdemir, Z. Guven; Canli, N. Yilmaz; Okutan, M.; Eran, B. Bilgin (TAYLOR & FRANCIS LTD, 2015)
Dielectric anisotropy properties and splay elastic constant, K-11 for 5CB (4-cyano-4'-pentylbiphenyl) plus 1% BAC(4-[4-(S)-2-methylbutoxybenzoyloxy]benzoic acid] have been investigated. The frequency dependent dielectric anisotropy and splay elastic constant have been calculated by using capacitance-voltage curves for various frequencies. The critical frequency, f(c) values of dielectric anisotropy for 4-cyano-4'-pentylbiphenyl (5CB) and 5CB+(1%)BAC composites were found to be 433.5 kHz and 439.5 kHz, respectively. It has been determined that BAC doping to 5CB decreases both threshold voltages and splay elastic constants for all frequencies applied. The decrease in K-11 values has been interpreted as the decrease of distortion in the system.
Keywords: 4-[4-(S)-2-Methylbutoxybenzoyloxy]benzoic liquid crystal acid; 5CB liquid crystal; dielectric anisotropy; splay elastic constant; PHASES; Chemistry; Crystallography; Materials Science